The impact of common success factors on overfunding in reward-based crowdfunding: An explorative study and avenues for future research - Felix Pinkow (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: While there is abundant literature on the key determinants of reward-based crowdfunding success, little research is dedicated to crowdfunding projects that are not only successful but receive significantly more funds than initially targeted through the defined funding goal. This study seeks to shed light on this vastly neglected topic in crowdfunding research. METHODOLOGY: Drawing on a rich dataset of 338 rewardbased crowdfunding projects, this study applied a two-step statistical analysis. First, regression analyses to determine relevant crowdfunding success factors were conducted in order to corroborate extant literature and to highlight that the data properly reflects the already identified key findings on crowdfunding success. In a second step, the very same factors were investigated for the case of overfunded projects, utilizing logistic regression analyses and a Blinder-Oaxaca Decomposition. FINDINGS: Although this study confirmed the findings of previous research considering the factors that increase the success probability of crowdfunding projects, the very same factors turned out to not explain the emergence of project overfunding. For instance, while project founders can provide updates, a higher number of different rewards, or utilize social media pages to increase the likelihood for success, these factors do not contribute to explain the phenomenon of project overfunding. IMPLICATIONS: The results of this study emphasize that in order to understand overfunding of crowdfunding projects, future research must go beyond the basic crowdfunding success factors. Building on the notion of the Two-Factor Theory, the findings suggest that the factors contributing to success can be considered hygiene factors that are required to succeed in the first place. However, these factors do not motivate the crowd to provide further funding to an already successful project. Hence the motivating factors remain yet unobserved in extant literature. In practice, this means that project teams achieving their funding goal cannot rely on the same factors that were helpful to succeed to encourage further funding from the crowd. The differentiation of hygiene and motivating factors for overfunding in reward-based crowdfunding offers rich opportunities for future research. More subjective factors, such as the individual perception of crowd members towards crowdfunding projects, are suggested to play an important role for the occurrence of project overfunding. ORIGINALITY/VALUE: By investigating project overfunding, this study addresses the research gap concerning the factors contributing to the emergence of project overfunding. There is little evidence on the characteristics of overfunded crowdfunding projects, and thus this study provides essential theoretical and empirical groundwork for future research to build upon this study’s results.